Risk Factor Assessment Causing Contract Change Orders in the Double-Double Track Project - Anggi Sanjaya; Wisnu Isvara (Publikasi Indonesia, 2024)
The Indonesian government is actively pursuing infrastructure development, with railway projects being a key focus due to their high demand in Jakarta and its surrounding regions. However, the complexity of railway projects often leads to delays and numerous changes, resulting in scope modifications that necessitate change orders, which have negative consequences for the project. Managing these risks effectively is essential to mitigate their impact on project costs and performance. This study proposes a solution through the application of risk management using a qualitative method known as the Probability Impact Matrix, which helps assess the most significant risks leading to change orders. The research aims to identify and assess the risks responsible for contract change orders in the Double-Double Track Development Project. It uses a mixed-method approach, focusing on two main phases: risk identification and risk assessment. The study examines five risk factors, including project-related factors (X1), owner-related factors (X2), contractor-related factors (X3), design-related factors (X4), and external factors (X5). The results demonstrate that all five variables significantly influence changes in project scope, with risk levels ranging from moderate to high. These findings provide valuable insights for project owners, consultants, contractors, and other stakeholders involved in construction project management. The study serves as a reference for decision-making and the implementation of control measures to minimize the negative impact of change orders.